Biogenic Amines Degradation by Lactobacillus plantarum: Toward a Potential Application in Wine - Capozzi, Vittorio; Russo, Pasquale; Ladero, Victor; Fernandez, Maria; Fiocco, Daniela; Alvarez, Miguel A.; Grieco, Francesco; Spano, Giuseppe (Frontiers in Microbiology, 2012)
Biogenic amines in wine represent a toxicological risk for the health of the consumer, with several trade implications. In this study 26 strains of Lactobacillus plantarum were analysed for their ability to degrade biogenic amines commonly found during wine fermentation. Two strains of L. plantarum were selected in reason of their ability to degrade putrescine and tyramine. The degradation was assessed in vitro, both in presence of the biogenic amines and in presence of the specific chemical precursor and of producer bacteria. The two L. plantarum biotypes were found capable to work synergically. In addition, the survival in wine-like medium and the aptitude to degrade malic acid after alcoholic fermentation of the selected L. plantarum strains was analysed. Our results suggest the potential application of wine L. plantarum strains to design malolactic starter cultures able to degrade biogenic amines in wine.